Peran Psikologi dalam Pendidikan Islam: Landasan Teoretis dan Implikasinya terhadap Proses Pembelajaran - Wijoyo, Muhammad Abdul Ghoffaar; Jajuli, Mohammad Syukron; Al Afdholi, Zakiyuddin; Suprayogi, Agus (TSAQOFAH, 2026)
Qur’anic memorization (tahfidz al-Qur’an) education is a form of Islamic education with distinctive scholarly characteristics that are deeply rooted in the pesantren tradition, yet in practice it is often understood merely in technical terms as the achievement of memorization targets, so that reflection on its epistemic foundations and educational values receives limited attention. This study aimed to analyze tahfidz education practices from the perspective of the philosophy of science by examining the epistemological, ontological, and axiological dimensions of education. A qualitative approach with a case study design was employed at Asrama Tahfidz Sunan Bonang Denanyar Jombang. Data were collected through observation, in-depth interviews, and documentation, and were analyzed descriptively–analytically using a reflective–philosophical approach. The findings show that tahfidz education rests on the authority of tradition and scholarly sanad as its primary sources of knowledge, views santri as spiritual subjects in the process of personality formation, and orients the educational process toward the internalization of noble values as its main goal. However, the strong emphasis on memorization targets has the potential to reduce the broader meaning of education and shift its value orientation from holistic character formation to purely technical achievement. Thus, engagement with the philosophy of science is required as a reflective framework to balance tradition, rationality, and values in tahfidz education practices, so that education is not only focused on the quantity of memorization but also on deepening meaning, character building, and the integration of knowledge.